Chronic Obstructive Pulmonary Disease Is Associated With Decreased Quality of Life in Bronchiectasis Patients: Findings From the KMBARC Registry - Kim, Sang Hyuk; Kim, Changhwan; Jeong, Ina; Lee, Seung Jun; Kim, Tae Hyung; Lee, Chang Youl; Oh, Yeon-Mok; Lee, Hyun; Kim, Youlim (Frontiers in Medicine, 2021)
Most studies have evaluated the impact of non-cystic fibrosis bronchiectasis (hereafter referred to as bronchiectasis) on quality of life (QoL) in patients with chronic obstructive pulmonary disease (COPD) using COPD cohorts. Accordingly, the impact of COPD on QoL in patients with bronchiectasis is not well elucidated. We used the Korean Multicenter Bronchiectasis Audit and Research Collaboration (KMBARC) registry between August 2018 and December 2019, a prospective observational cohort that enrolled patients with bronchiectasis in Korea. We evaluated co-occurrence exposure to COPD in bronchiectasis patients, and the primary outcome was QoL according to the Bronchiectasis Health Questionnaire (BHQ). We also investigated factors associated with decreased QoL, defined as the lowest quartile of the total BHQ score. Of 598 patients with bronchiectasis, 372 (62.2%) had COPD. Bronchiectasis patients with COPD had a significantly lower total BHQ score compared with those without COPD (median = 63.1 [interquartile range: 54.8–68.6] vs. 64.8 [57.4–70.8], p = 0.020). Multivariable analysis revealed that dyspnea (adjusted odds ratio [aOR] = 3.21, 95% confidence interval [CI] = 1.21–8.60), depression (aOR = 1.28, 95% CI = 1.16–1.44), and fatigue (aOR = 1.05, 95% CI = 1.01–1.09) were significantly associated with decreased QoL in bronchiectasis patients with COPD. In conclusion, bronchiectasis patients with COPD had significantly decreased QoL than patients without COPD. In bronchiectasis patients with COPD, dyspnea, depression, and fatigue were associated with decreased QoL.